2012
DOI: 10.1007/s00167-012-2243-8
|View full text |Cite
|
Sign up to set email alerts
|

Nerve injury during hamstring graft harvest: a prospective comparative study of three different incisions

Abstract: Therapeutic randomized controlled prospective study, level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 28 publications
4
94
0
Order By: Relevance
“…These branches originate from the saphenous nerve (IPSBN: infrapatellar branch of saphenous nerve) and medial femoral cutaneous nerve (SBSN: sartorial branch of sensory nerve) [ 20 , 24 ]. While an oblique incision has less incidence of IPSBN transections, injury to SBSN is not affected by the type of incision used [ 27 ]. In any case, and in agreement with our own observations, it has been concluded that daily living is nothing or only slightly affected by these sensory changes [ 21 ].…”
Section: Skin Incisionsupporting
confidence: 87%
“…These branches originate from the saphenous nerve (IPSBN: infrapatellar branch of saphenous nerve) and medial femoral cutaneous nerve (SBSN: sartorial branch of sensory nerve) [ 20 , 24 ]. While an oblique incision has less incidence of IPSBN transections, injury to SBSN is not affected by the type of incision used [ 27 ]. In any case, and in agreement with our own observations, it has been concluded that daily living is nothing or only slightly affected by these sensory changes [ 21 ].…”
Section: Skin Incisionsupporting
confidence: 87%
“…The characteristics of the studies included in the meta‐analysis are summarized in Table . Eleven studies ( n = 1,050 patients) reported such . The postoperative follow‐up time for patients in the studies ranged from 6–78 months.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies ( n = 305 patients) directly compared the rate of iatrogenic IPBSN injury during the procedure with vertical versus horizontal incisions. Similarly, 4 studies ( n = 245 patients) directly compared the rate of such injury with vertical versus oblique incision orientations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not represent the actual rate of dysesthesia found in these patients, taking into account the possibility of neurological recovery that can occur in the first two years after surgery 16 . Furthermore, the functional impact in patients with neurological deficit was not measured and, finally, this study did not assess the possible involvement of the saphenous nerve due to the use of a stripper to collect graft, which could perhaps explain the lower rate of dysesthesia, albeit still present, found in the group in which the oblique incision was used 17, 18…”
Section: Discussionmentioning
confidence: 99%